(untitled) (Research in Agriculture Livestock and Fisheries, 2021)
The experiment was carried out during the period of December to May 2019 at the BINA substation Magura farm and farmers’ field sottopur, sadar, Magura in a randomized complete block design with three replications. The experiment was conducted to study the effect of planting time on the yield and yield attributes along with three sowing time viz. 15 December, 25 December, 05 January and transplanting was done on 24 Jan.; 03 Feb.; 13 Feb. in the main field along with three varieties viz. Binadhan -17, Binadhan-18, BRRIdhan-29. From on farm trial, it revealed that; The transplanting time of February 03 have found more yield and duration (7.62t/ha and 142 days) and transplanting time of January 24 have found have yield and duration 7.59 t/ha and 147 days which was statistically same; lowest yield found in February 13 that was 6.89t/ha and duration 136 days. From on station trial, it revealed that; the January 24 transplanting date was found more yield and duration (7.28t/ha and 147days) and February 03 was found (6.06t/ha and 142 days); lowest yield was found in February 13 transplanting date that was (4.5t/ha and 136 days). From both results discussion, it concluded that Transplanting at January 24 would be the optimum time along with different planting time of Binadhan-17 in Maguraregion. Res. Agric., Livest. Fish.8(1): 19-24, April 2021